2016
DOI: 10.1002/jcph.789
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety Assessment ofl-Tetrahydropalmatine in Cocaine Users: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Cocaine use disorder (CUD) remains a significant public health challenge. Levo-tetrahydropalmatine (L-THP), a well-tolerated and non-addictive compound, shows promise for the management of CUD. Its pharmacologic profile includes blockade at dopamine and other monoamine receptors and attenuation of cocaine self-administration, reinstatement, and rewarding properties in rats. This study evaluated the safety of L-THP in human cocaine users and its influence on the safety and pharmacokinetics (PK) of cocaine. Twen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…11) According to previous phytochemical investigations, several natural alkaloids, including crebanine (CN), O-methylbulbocapnine (OMP), dicentrine (DC), tetrahydropalmatine (THP), and N-methyl tetrahydropalmatine (NTHP) have been found in the tubes of S. vernosa. [12][13][14] CN, OMP, and DC are aporphine alkaloids and they show the structural differences in the position of the dimethoxy group on the D-ring. Whereas, THP and NTHP are derivatives of protoberberine alkaloids and differ only the presence or absence of methyl group on the quaternary nitrogen atom in the position 7.…”
mentioning
confidence: 99%
“…11) According to previous phytochemical investigations, several natural alkaloids, including crebanine (CN), O-methylbulbocapnine (OMP), dicentrine (DC), tetrahydropalmatine (THP), and N-methyl tetrahydropalmatine (NTHP) have been found in the tubes of S. vernosa. [12][13][14] CN, OMP, and DC are aporphine alkaloids and they show the structural differences in the position of the dimethoxy group on the D-ring. Whereas, THP and NTHP are derivatives of protoberberine alkaloids and differ only the presence or absence of methyl group on the quaternary nitrogen atom in the position 7.…”
mentioning
confidence: 99%
“…The similarity values of 21 samples exceeded 0.9, i.e., similar components were present in these samples regardless of geographic location. However, low similarity values of <0.9 observed for samples 14,16,20, and 21 suggested that the compositions of these samples might be different from those of samples with high similarity values. Thus, crude herbs and prepared slices were concluded to be significantly different because of the production process and the variable contents of main bioactive constituents.…”
Section: Hplc Fingerprint Establishment and Similarity Analysis (Sa)mentioning
confidence: 96%
“…Samples 1-8 and 22-23 were unprocessed (crude drugs), 9-20 were boiled (cooked drugs), and sample 21 was sulfur-fumigated. For better comparison, we used samples originating from Zhejiang, excluding those produced outside of this province (samples [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. It seemed the fingerprints of crude drugs and cooked medicines were obviously different in areas A and C (see Supplementary Fig.…”
Section: Hplc Fingerprint Establishment and Similarity Analysis (Sa)mentioning
confidence: 99%
See 1 more Smart Citation
“…L-isocorypalmine is also one of the active metabolites of L-tetrahydropalmatine with a mono demethylation at C-2 site [7]. Several animal studies have supported the therapeutic potential of L-tetrahydropalmatine to treat addiction, and phase І clinical trial has been conducted in healthy men and cocaine users [1,2,8,9].…”
Section: Introductionmentioning
confidence: 99%